Data Security Model Using (AES-LEA) Algorithms for WoT Environment - Zinah A. Al-jazaeri; Joolan Rokan Naif; Ahmad Mohamad Ghandour (Iraqi Journal for Computers and Informatics)
The Web of Things WoT connects physical objects and displays them in the WWW. The growing number of Internet of Things IoT devices and data sharing has led to the attack on sensitive information and allowing unauthorized persons to access and manipulate it. Therefore, ensuring data privacy and protection is a major challenge for organizations and individuals. This paper presents a new hybrid method for the encryption of information to be more suitable for embedded devices in the WoT environment by modifying the Advanced Encryption Standard AES algorithm and hybridizing it with the Lightweight Encryption Algorithm LEA algorithm as well as the Secure Hash Algorithm version 3 SHA3-256 algorithm for integrity and using four dimensional-NSJR system for generation of chaos keys. The proposed method is designed to decrease encryption /decryption time for the information transmitted in the WoT environment and in areas such as government data that need protection against attacks. The proposed method comprises three sub-layers: Chaos Keys generation layer, Data encryption layer, and Authentication layer. The proposed method passed all 15 NIST ( National Institute of Standards & Technology) tests. The amount of time needed to encrypt and decrypt the proposed method was compared with the original encryption methods for different data sizes and five sensitivity levels, and the proposed encryption method was found to be up to (150%) faster while maintaining security strength.